Warming Up dengan Motivasi Belajar Senam Pada siswa Kelas XI SMAN 1 Cilamaya: Warming Up with the motivation to learn gymnastics on sophomeres 1 1 cilamaya - Ihan Dwi Kurniawan; Akhmad Dimyati; Aria Kusuma Yuda (Universitas Singaperbangsa, 2020)
The purpose of this study was carried out with the following objectives, To find out how important warming is in improving one's skills in learning physical sports and health education at SMA Negeri 1 Cilamaya. To answer the formulation of research problems that have been formulated, the author uses the quantitative approach correlation research method. Based on the analysis of the data presented above, the results of research on the relationship between Warming Up and Gymnastics Learning Motivation for SMA Negeri 1 Cilamaya students on the Warming Up variable obtained a maximum score of 149 and a minimum score of 90, the average of 118 standard deviations of 12.58. As for the variable Gymnastics Learning Motivation obtained a maximum of 149 and a minimum score of 90, the average of 118 standard deviations of 12.58. Keywords 1: Warming Up, Person correlation design, Gymnastic Learning Motivation